2020
DOI: 10.1101/2020.10.01.322859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The GARP Domain of the Rod CNG Channel’s β1-subunit Contains Distinct Sites for Outer Segment Targeting and Connecting to the Photoreceptor Disc Rim

Abstract: Vision begins when light is captured by the outer segment organelle of photoreceptor cells in the retina. Outer segments are modified cilia filled with hundreds of flattened disc-shaped membranes. Disc membranes are separated from the surrounding plasma membrane and each membrane type has unique protein components. The mechanisms underlying this protein sorting remain entirely unknown. In this study, we investigated the outer segment delivery of the rod cyclic nucleotide-gated (CNG) channel, which is located i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Both PRCD and GC1 require rhodopsin for their stability and trafficking to the OS (Pearring et al, 2015 ; Spencer et al, 2016 ). A recent study confirmed trafficking of GC1 through the conventional pathway (Pearring et al, 2020 ).…”
Section: Intrinsic Membrane Protein Compartmentalization Within the Cmentioning
confidence: 69%
See 2 more Smart Citations
“…Both PRCD and GC1 require rhodopsin for their stability and trafficking to the OS (Pearring et al, 2015 ; Spencer et al, 2016 ). A recent study confirmed trafficking of GC1 through the conventional pathway (Pearring et al, 2020 ).…”
Section: Intrinsic Membrane Protein Compartmentalization Within the Cmentioning
confidence: 69%
“…Until recently, peripherin 2 was the only OS-destined protein identified that is transported through the unconventional pathway. However, evidence suggests that R9AP traffics to the OS independently of rhodopsin, suggesting that it may transport via the unconventional secretory pathway (Pearring et al, 2014 ) and a recent study has shown that ABCA4 also traffics via the unconventional pathway (Pearring et al, 2020 ).…”
Section: Intrinsic Membrane Protein Compartmentalization Within the Cmentioning
confidence: 99%
See 1 more Smart Citation